Investigating the role and regulation of GPNMB in progranulin-deficient macrophages - Gillett, Drew A.; Neighbarger, Noelle K.; Cole, Cassandra; Wallings, Rebecca L.; Tansey, Malú Gámez (Frontiers in Immunology, 2024)
Introduction Progranulin (PGRN) is a holoprotein that is internalized and taken to the lysosome where it is processed to individual granulins (GRNs). PGRN is critical for successful aging, and insufficient levels of PGRN are associated with increased risk for developing neurodegenerative diseases like AD, PD, and FTD. A unifying feature among these diseases is dysregulation of peripheral immune cell populations. However, considerable gaps exist in our understanding of the function(s) of PGRN/GRNs in immune cells and their role in regulating central-peripheral neuroimmune crosstalk. One of the most upregulated genes and proteins in humans with GRN haploinsufficiency and in aged Grn knock-out (KO) mice is glycoprotein non-metastatic B (GPNMB) but its normal role within the context of immune crosstalk has not been elucidated. Methods To address this gap, peritoneal macrophages (pMacs) from 5-to-6-month old WT and Grn KO mice were assessed for Gpnmb expression and stimulation-dependent cytokine release in the presence or absence of the Gpnmb extracellular domain (ECD). Cellular localization, as well as inhibition of, the microphthalmia-associated transcription factor (MITF) was assessed to determine its mechanistic role in Gpnmb overexpression in Grn KO pMacs. Results We observed an increase in GPNMB protein and mRNA as a result of insufficient progranulin in peripheral immune cells at a very early age relative to previous reports on the brain. Stimulation-dependent cytokine release was decreased in the media of Grn KO pMacs relative to WT controls; a phenotype that could be mimicked in WT pMacs with the addition og GPNMB ECD. We also found that MITF is dysregulated in Grn KO pMacs; however, its nuclear translocation and activity are not required to rescue the immune dysregulation of Grn KO macrophages, suggesting redundancy in the system. Discussion These findings highlight the fact that knowledge of early-stage disease mechanism(s) in peripheral populations may inform treatment strategies to delay disease progression at an early, prodromal timepoint prior to development of neuroinflammation and CNS pathology.